2017
DOI: 10.5897/jpp2017.0452
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents and biological activities of different solvent extracts of Prosopis farcta growing in Egypt

Abstract: Different solvent extracts from the aerial part of Prosopis farcta growing in Egypt have been biologically evaluated by studying their antimicrobial, anticancer and antioxidant activities. Furthermore, the chemical analysis using GC/MS has been performed for the promising extracts n-hexane and methylene chloride, and this analysis led to the identification of twenty six and thirty two compounds respectively from n-hexane and methylene chloride. The major compound identified in the n-hexane is (Z) 9,17octadecad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 23 publications
1
11
6
Order By: Relevance
“…Each extract was more active than others against specific bacteria. 28 MeOH and nhexane extracts of aerial parts were prepared and tested against the major pathogenic bacteria of fish, including A. hydrophila, Y. ruckeri and S. iniae. MeOH extract was more active.…”
Section: Antibacterialmentioning
confidence: 99%
See 2 more Smart Citations
“…Each extract was more active than others against specific bacteria. 28 MeOH and nhexane extracts of aerial parts were prepared and tested against the major pathogenic bacteria of fish, including A. hydrophila, Y. ruckeri and S. iniae. MeOH extract was more active.…”
Section: Antibacterialmentioning
confidence: 99%
“…31 Anticancer Among extracts of aerial parts that were prepared with six different solvents, the EtOAc extract had the highest activity. 28 All plant aq. EtOH (80 %, v/v) extract was active against HT-29 cancer cell lines.…”
Section: Antibacterialmentioning
confidence: 99%
See 1 more Smart Citation
“…The compound 2,4-Dimethylhept-1-ene is reported to play a role in human metabolites [ 49 ]. In contrast, tetradecane is noted as a phytochemical found in Prosopis farcta plants [ 50 ] and almonds [ 51 ]. Furthermore, a study reported that 2,4-Di-tert-butyl phenol is an antifungal and antioxidant bioactive compound purified from a newly isolated Lactococcus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Prosopis farcta (family Fabaceae) is a well-known medicinal plant that grows in Jordan, Kuwait, Turkey, Iraq, Northern Africa, South Western Asia, and Iran (Khuzestan, Gilan, Fars, Hormozgan, Baluchestan, Khorasan, and Tehran provinces). e plant commonly known by its local name as the "Syrian mesquite" generally grows in warm and dryer climate [9].…”
Section: Introductionmentioning
confidence: 99%